Validation of a Swahili version of the World Health Organization 5-item well-being index among adults living with HIV and epilepsy in rural coastal Kenya - Esther Chongwo; Derrick Ssewanyana; Carophine Nasambu; Patrick N. Mwangala; Paul M. Mwangi; Moses K. Nyongesa; Charles R. Newton; Amina Abubakar (BMC, 2018)
Abstract Objective The purpose of this study was to evaluate the psychometric properties of the World Health Organization's five item well-being index (WHO-5) when administered to adults living with HIV or epilepsy in a rural setting at the coast of Kenya. Methods A case control study design was conducted among 230 adults aged 18-50 years, who comprised 147 cases (63 living with epilepsy and 84 living with HIV) and 83 healthy controls. The participants were administered to a face-to-face interview during which they completed the Swahili version of WHO-5 well-being index, the Major Depression Inventory (MDI) and responded to some items on their socio-demographic characteristics. Analysis to assess internal consistency, construct validity, discriminant validity, and convergent validity of the Swahili version of WHO-5 well-being index was conducted. A multivariate regression was carried out to assess the association between psychological wellbeing (assessed using Swahili version of WHO-5 well-being index) and having a chronic illness (HIV or epilepsy). Results The Swahili version of WHO-5 well-being index demonstrated good internal consistency with Cronbach alpha ranges of 0.86-0.88 among the three study groups. The tool had good discriminant validity. A one factor structure of the tool was obtained from confirmatory factor analysis (overall Comparative Fit Index = 1.00, Tuckler Lewis Index = 1.01, Root Mean Square of Error Approximation = 0.00). Living with HIV or epilepsy in comparison to being a healthy control was significantly associated with greater odds of having sub-optimal psychological wellbeing. Conclusion Our findings demonstrate that the Swahili version of WHO-5 well-being index has good psychometric properties and is appropriate for use to evaluate psychological well-being among adults living with chronic conditions such as HIV or epilepsy from a rural low resource setting in Kenya. Given its brevity and ease of use, the Swahili version of WHO-5 well-being index could potentially be used by lay workers and other paraprofessional to monitor psychological well-being among chronically ill adults in resource poor settings.